INFORMATION AND TRAINING NEEDS OF COTTON FARMERS ON THEIR FARMING ACTIVITIES IN ZAMBIA - Stephen Oluseun ADEOGUN; Olaoluwa Ayodeji ADEBAYO; Matthew Olalekan OOSE; Bolaji Grace ABIONA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Nigeria, households’ per capita calorie consumption is below the required level and this in turn has reduced food security and productivity among households. Rice is a high calorie given food item that has contributed to the improved nutrional status and welfare of Nigerians. Therefore, the study determined the demand for rice in Nigeria as a means of enhancing calorie intake and food security status among households. The study used Harmonised National Living standard survey (HNLSS) data obtained from National Bureau of Statistics. 32,012 households comprising rural (24,941) and urban (8,071) sectors were used. The methods of data analysis include descriptive statistics, probit regression analysis and Quadratic Almost Ideal Demand System (QUAIDS.) The study revealed that Per-capita expenditure on rice is lowest among rural (N2, 275.48) and North-west (N2, 019.17) residents. It is also lower among male headed households. Rice is a necessity (0.801) and could serve as substitute for luxury food items such as beans (0.919) and other cereals (0.199). Gender, sectoral and regional food policy measures should be options in increasing rice demand among households in Nigeria in order to ensure increase per calorie intake.